Proceedings of the 2017 International Seminar on Social Science and Humanities Research (SSHR 2017) 2018
DOI: 10.2991/sshr-17.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Medical Students' Family Cohesion, Adaptation and Learning Burnout: the Mediating Effect of Psychological Resilience

Abstract: Objective To investigate the characteristics of resilience family cohesion, adaptability and learning burnout,and analyse the relationship among them. Methods: One thousand six hundred and twenty-five undergraduates who were collected from Seven Universities in Guangdong by stratified random sampling method were investigated with Learning Burnout Scale for Chinese Undergraduates (LBSCU), Family Adapation and Cohension Scale, Second Edition-Chinese Version (FACESII-CV) and Resilience Scale for Chinese Adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In this study, we examined the association between the functioning of the family environment and academic burnout among college students and the underlying mediating mechanisms. Generally consistent with previous findings ( Hou and Liang, 2017 ; Aunola et al, 2018 ), participants in families with higher cohesion and adaptability tend to show less emotional, behavioral, or cognitive burnout symptoms in learning. We further found that family cohesion and adaptability do not directly affect academic burnout, but indirectly exert effects through increasing intrapersonal resources (i.e., PsyCap) and interpersonal resources (i.e., peer support).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we examined the association between the functioning of the family environment and academic burnout among college students and the underlying mediating mechanisms. Generally consistent with previous findings ( Hou and Liang, 2017 ; Aunola et al, 2018 ), participants in families with higher cohesion and adaptability tend to show less emotional, behavioral, or cognitive burnout symptoms in learning. We further found that family cohesion and adaptability do not directly affect academic burnout, but indirectly exert effects through increasing intrapersonal resources (i.e., PsyCap) and interpersonal resources (i.e., peer support).…”
Section: Discussionsupporting
confidence: 91%
“…Family cohesion was found to affect individual resilience through perceived social support and self-esteem ( Wei, 2021 ). Another study supported the argument that psychological resilience exerts a mediating effect on the link between family cohesion and adaptability and academic burnout with the cultivation of coping ability and emotional support ( Hou and Liang, 2017 ). Besides, it was found in research among patients and relocating women that perceived social support was positively correlated to overall PsyCap and its components, hope, self-efficacy, resilience, and optimism ( Foote et al, 1990 ; Schönfeld et al, 2017 ; Sagi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been established that academic adaptability is negatively related to learning burnout. 8 , 15 , 17 Hou and Liang 18 hold a similar view. They also argue that learning burnout is the result of individuals’ inability to cope with learning difficulties.…”
Section: Introductionmentioning
confidence: 76%
“…A functional family serves as a protective factor against academic burnout, and helps the student to develop proper autonomy and adequate problem-solving strategies. These may shape the student’s resilience to deal with university demands, difficult issues and academic pressure [ 46 , 64 ].…”
Section: Discussionmentioning
confidence: 99%